Seen in a New Light: Patterns of Adult Participation in Higher Education - David S. Stein; Lynn A. Trinko; Constance E. Wanstreet (Adult Education Research Conference, 2008)
This study identified length of time out of school and institutional support among the factors associated with the decision to enroll in a higher education degree program. The study suggests that considering participation in the context of social capital can help adult educators better understand enrollment decisions.
Keywords: decision-making process; higher education; predicting enrollment; social capital; workforce development